Physiological benefits and performance of sea water ingestion for athletes in endurance events: A systematic review - Agarón-Vela, J.; González-Acevedo, O.; Plaza-Diaz, J.; Casuso, R. A.; Huertas, J. R.. (Nutrients, 2022)
In different endurance events, athletes have limited access to fluid intake, such as ultra-endurance running. For this reason, it is necessary to establish an adequate hydration strategy for this type of long-duration sporting event. Indeed, it seems that the intake of seawater is a suitable hydration alternative to improve post-exercise recovery in this type of endurance event. This seawater is characterized by being a deep natural mineral water of moderate mineralization, which is usually extracted from a depth of about 700 m. Therefore, the aim of this systematic review is to evaluate the efficacy of seawater consumption in both performance and post-exercise recovery in long-duration sport events. A systematic and comprehensive literature search was performed in PubMed, Scopus, and Web of Science in September 2022. Initially, 8 out of 558 articles met the inclusion criteria. Among these eight studies, six were randomized clinical trials, and two were observational studies (one cross-sectional and one prospective study in well-conditioned student athletes). The results showed that deep sea water consumption accelerated the recovery of aerobic capacity and leg muscle capacity on running performance. In addition, the lactate production after the running exercise in seawater was significantly lower than in pure water. In conclusion, the present review demonstrates that seawater consumption could significantly improve the capacity of recovery after exercise.